Piezoelectric bioMEMS cantilever for measurement of muscle contraction and for actuation of mechanosensitive cells. (December 2019) - Coln, Elizabeth A.; Colon, Alisha; Long, Christopher J.; Sriram, Narasimhan Narasimhan; Esch, Mandy; Prot, Jean-Matthieu; Elbrecht, Daniel H.; Wang, Ying; Jackson, Max; Shuler, Michael L.; Hickman, James J.
Abstract: Abstract : A piezoelectric biomedical microelectromechanical system (bioMEMS) cantilever device was designed and fabricated to act as either a sensing element for muscle tissue contraction or as an actuator to apply mechanical force to cells. The sensing ability of the piezoelectric cantilevers was shown by monitoring the electrical signal generated from the piezoelectric aluminum nitride in response to the contraction of iPSC-derived cardiomyocytes cultured on the piezoelectric cantilevers. Actuation was demonstrated by applying electrical pulses to the piezoelectric cantilever and observing bending via an optical detection method. This piezoelectric cantilever device was designed to be incorporated into body-on-a-chip systems.